Effects of Molecular Hydrogen on Methamphetamine-Induced Neurotoxicity and Spatial Memory Impairment - Wen, Di; Hui, Rongji; Wang, Jian; Shen, Xi; Xie, Bing; Gong, Miao; Yu, Feng; Cong, Bin; Ma, Chunling (Frontiers in Pharmacology, 2019)
Methamphetamine (METH) is a highly addictive stimulant, and METH exposure can induce irreversible neuronal damage and cause neuropsychiatric and cognitive disorders. The ever-increasing levels of METH abuse worldwide have necessitated the identification of effective intervention strategies to protect the brain against METH-induced neurotoxicity. The protective effects of molecular hydrogen on oxidative stress and related neurodegenerative diseases have been recently elucidated. Herein, we investigated whether treatment with molecular hydrogen ameliorated the METH-induced neurotoxicity and spatial learning and memory impairments. Male C57BL/6 mice received four intraperitoneal METH injections (10 mg/kg, 3-h interval), and stereotypic behaviors and hyperthermia were observed. After METH treatment and behavioral observation, the mice were returned to their home cages, where they received water or hydrogen-rich water (HRW) ad libitum for seven days. We found that the molecular hydrogen delivered by ad libitum HRW consumption significantly inhibited the METH-induced spatial learning impairment and memory loss evidenced in the Barnes maze and Morris water maze tests. Furthermore, molecular hydrogen significantly restrained the neuronal damage in the hippocampus after high-dose METH exposure. Ad libitum HRW consumption also had an inhibitory effect on the METH-induced increase in the expression of Bax/Bcl-2, cleaved caspase-3, glucose-related protein 78 (GRP 78), CCAAT/enhancer-binding protein homologous protein (CHOP), and p-NF-kB p65 expression and elevation of interleukin (IL)-6 and tumor necrosis factor (TNF)-a levels in the hippocampus. These are the first findings to indicate that hydrogen might ameliorate METH-induced neurotoxicity and have a potential application in reducing the risk of neurodegeneration frequently observed in METH abusers